THE INFLUENCE OF STUDENTS' LEARNING DISCIPLINE ON LEARNING ACHIEVEMENT IN SOCIAL STUDIES SUBJECT AMONG GRADE VII STUDENTS AT SMP NEGERI 10 PEMATANGSIANTAR - Theresi; Anggun Tiur Ida Sinaga; Injen Pardamean Butabutar (RADJA PUBLIKA, 2025)
This study aims to examine the effect of learning discipline on students’ academic achievement. The research instruments used were a learning discipline questionnaire and an academic achievement questionnaire, both of which had been tested for validity and reliability with satisfactory results. The normality test using the Kolmogorov-Smirnov method indicated that the data were normally distributed, with a significance value of 0.200 greater than 0.05. Simple linear regression analysis produced the equation Y = 60.135 + 0.258X, which demonstrates a positive relationship between learning discipline and academic achievement. The regression significance test showed that the t-value of 11.417 was greater than the t-table value of 1.67203 at a 5% significance level, and the significance value of 0.002 was less than 0.05, indicating that learning discipline has a positive and significant effect on academic achievement. The coefficient of determination (R Square) was 0.150, meaning that learning discipline contributed 15% to academic achievement, while the remaining 85% was influenced by other factors outside the scope of this study.